Cascade Fuzzy Controller based Vibration reduction in Switched Reluctance Motor Drive in Electric Screw Press Machine - et al., Uma J (International Journal of Advanced Science and Technology, 2019)
This paper presents the cascade fuzzy controller based switching angle compensator for reducing the torque ripples and vibrations of the SRM drive used in electric screw machine. The switching angle such as Turn- ON and Turn-OFF angle of the motor are automatically changed with respect to speed and current values. Cascade fuzzy controller consists of two fuzzy controller connected in series, the first controller tune the Turn-OFF angle according to the speed and current changes and second controller tune the Turn-ON angle according to the tuned Turn-OFF angle and current value. The vibration of the motor under different load conditions and FFT spectrums of measured vibration signals are calculated. The proposed algorithm has been tested through the MATLAB simulation. A simulation results are proved that the proposed switching angle compensator can increases the performance of drives in terms of less speed oscillation, less torque ripples and less vibration even at low speed in steady state condition than the constant switching angle method.